Pengaruh Jumlah Penduduk, Pendapatan Asli Daerah, Efisiensi Keuangan, dan Biaya Barang dan Jasa terhadap Kondisi Keuangan Pemerintah Daerah di Indonesia - Angrainy, Chindy; Deviani, Deviani (Jurnal Eksplorasi Akuntansi, 2025)
This research aims to determine the influence of population, local original income, financial efficiency, and costs of goods and services on the financial condition of Regional Governments in Indonesia. The research population is all cities/regencies on the island of Java in 2022. This research uses secondary data with documentation techniques. The analysis technique used is multiple linear regression analysis. The results of the research show that local revenue has a positive effect on the financial condition of regional governments on the island of Java. Meanwhile, population, financial efficiency and costs of goods and services have no effect on the financial condition of local governments on the island of Java. This research contributes to increasing insight and knowledge in the field of accounting, especially public sector accounting, regarding what influences influence the financial conditions of local governments.